Analisis hubungan status gigi dengan pola makan dan asupan nutrisi pada manula suku Bugis dan suku Mandar - Bahruddin Thalib (Journal of Dentomaxillofacial Science, 2008)
The main function of teeth is chewing, whereas its capabilities depends on amount ofteeth remains. High teeth loss in elderly can compromise this chewing function,resulting in inadequate nutrition intake. Analytic epidemiology study of relationshipbetween dental status, diet pattern and nutrition intake in elderly of Buginese andMandarnese took 424 sample (Buginese 206; Mandarnese 216). Buginese dentalstatus showed higher prevalence of tooth loss 0-10 than Mandarnese (24.5%:18.1%),as for tooth loss 11-20 and 21-27, Mandarnese dental status showed higherprevalence than Buginese, and for total tooth loss Buginese showed higher prevalencethan mandarnese. Total mean tooth loss between Mandarnese and Buginese not somuch different, which is 20.42 to 19.58. Generally no significant diet patterndifference found between Buginese and Mandarnese. Diet pattern consist of foodprocessed to meet elderly chewing capabilities. Analysis of relationship betweendental status and macro nutrient carbohydrate and protein intake showed significantrelation (p<0.05), as for lipid intake showed relation although not significant.Analysis of relationship between dental status and micro nutrient Vitamin D, E, and Cstatically showed no significant relation, Vitamin A showed no relation at all.